Samomorilnost v Sloveniji - Ziherl, Slavko (Zdravniški vestnik, 2010)
Background: The prevalence of suicide is increasing worldwide and nowadays approximately one million people commit suicide every year. In Slovenia, suicide is a major public health and social problem. Suicide rate in Slovenia is among the highest in Europe. Despite intensive research work on suicide in the countries with high suicide rates and despite all new data on risk factors, the suicide rates do not decline (with few exceptions). Nevertheless,suicide prevention is possible if it is based on research data and included in the National programme of suicide prevention. Conclusions: Slovenia being highly endangered by suicide, its Gorvernment should immediately nominate a working group which would prepare a National programme of suicide prevention.
Keywords: Dejavniki tveganja; Duševne motnje; Epidemiology; Mental Disorders; Prevention And Control; Risk Factors; Samomor; Samomor, poskus; samomorilno vedenje; samomorilnost; Slovenia; Slovenija; Suicide; Suicide, Attempted